1954
DOI: 10.2307/4588924
|View full text |Cite
|
Sign up to set email alerts
|

Medical Aspects of Excessive Fluoride in a Water Supply

Abstract: Tex., reported lhere is one of several related studies designed to provide information on the effects of excessive amounts of fluoride occurring naturally in a water supply.Previous investigations (1-3) indicate a need

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1964
1964
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…Crippling deformities of the skeleton such as kyphosis, stiffness of the spine, reduced mobility of bony cage, and bony exostoses are reported to be some of the clinical features of skeletal fluorosis. No evidence of skeletal fluorosis was found in residents of Bartlett, Texas, exposed to 8 J.lg F/ml in the drinking water for 15 years (Leone et al, 1954), or in life long residents of North Dakota exposed to a 4.0-5.8 J.lg F/ml in the drinking water (Bernstein et al, 1966). However, in an area in India, with 2.5-5.0 J.lg F/ml in the drinking water, 32 percent of the people examined exhibited osteosclerosis (Pandit et al, 1940).…”
Section: Safe and Optimal Levels Of Fluoride Ingestionmentioning
confidence: 99%
“…Crippling deformities of the skeleton such as kyphosis, stiffness of the spine, reduced mobility of bony cage, and bony exostoses are reported to be some of the clinical features of skeletal fluorosis. No evidence of skeletal fluorosis was found in residents of Bartlett, Texas, exposed to 8 J.lg F/ml in the drinking water for 15 years (Leone et al, 1954), or in life long residents of North Dakota exposed to a 4.0-5.8 J.lg F/ml in the drinking water (Bernstein et al, 1966). However, in an area in India, with 2.5-5.0 J.lg F/ml in the drinking water, 32 percent of the people examined exhibited osteosclerosis (Pandit et al, 1940).…”
Section: Safe and Optimal Levels Of Fluoride Ingestionmentioning
confidence: 99%
“…The authors concluded that roentgenographic evidence of bone changes can be produced by excessive fluoride in water, but in "only a select few (10 to 15% of those exposed)". These skeletal changes were not associated with other physical findings, even though the fluoride content in bone could be six times "normal" (Leone et al, 1954 and1955). Stevenson and Watson (1957) reviewed 170 000 roentgenographs obtained in one hospital between 1943 and 1953 and identified 23 cases of osteosclerosis.…”
Section: Skeletal Fluorosismentioning
confidence: 81%
“…For example, a study in Bartlett, Texas, 4 reported on potential health efl l fects in people with longlterm residence In the light of these and similar studies it was not surprising that a hypothesis was formulated that the adl l justment of the fluoride level of public drinkinglwater supplies to 1 mg/l might have similar effects to naturally fluoril l dated water. To test this, a controlled community water fluoridation trial in the city of Grand Rapids started on 25 January 1945, with the nearby city of Muskegon acting as a control.…”
Section: One In a Million: The First Community Trial Of Water Fluoridmentioning
confidence: 99%